2006
DOI: 10.1080/09513590600733357
|View full text |Cite
|
Sign up to set email alerts
|

Pro12Ala polymorphism of the peroxisome proliferator-activated receptor-γ gene in women with polycystic ovary syndrome

Abstract: We suggest that Pro12Ala polymorphism of the PPAR-gamma gene may be a modifier of insulin resistance in women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 38 publications
(86 reference statements)
4
40
2
Order By: Relevance
“…A significantly lower occurrence of variant genotypes and lower Ala allele frequency of Pro12Ala polymorphism among PCOS women in our study cohort and its significant association with reduced risk of PCOS is in agreement with previous findings in Finnish [17], Turkish [34] and Korean [12] women. Recently, a study from South India showed marginally significant difference in allelic (p=0.05) but not in the genotypic frequency (p=0.23) of this polymorphism in PCOS women (n=243) as compared to controls (n=281) [6].…”
Section: Association Of Pparγ Pro12ala C/g Polymorphism With Pcos Andsupporting
confidence: 81%
See 1 more Smart Citation
“…A significantly lower occurrence of variant genotypes and lower Ala allele frequency of Pro12Ala polymorphism among PCOS women in our study cohort and its significant association with reduced risk of PCOS is in agreement with previous findings in Finnish [17], Turkish [34] and Korean [12] women. Recently, a study from South India showed marginally significant difference in allelic (p=0.05) but not in the genotypic frequency (p=0.23) of this polymorphism in PCOS women (n=243) as compared to controls (n=281) [6].…”
Section: Association Of Pparγ Pro12ala C/g Polymorphism With Pcos Andsupporting
confidence: 81%
“…It is well established that Ala allele, enhances insulin sensitivity and protects against development of T2DM [28]. Increased insulin sensitivity, decreased fasting insulin levels, HOMA-IR, [13,14,17,30,34] basal metabolic rate [16] and increased HDL-C levels [4] were observed in women with PCOS who were carriers of Ala alleles. Consistently we too observed that the variant genotype carriers had significantly lower 2 h glucose levels than wild genotype carriers in PCOS group but not in controls.…”
Section: Association Of Pparγ Pro12ala C/g Polymorphism With Pcos Andmentioning
confidence: 99%
“…Problematic to genetic association studies are differences in ethnic background and small sample sizes, both of which can lead to spurious results. Whereas most studies (9)(10)(11)(12)14,15), present study included, reported no association between Pro12Ala genotype and PCOS diagnosis, a few reported that the Pro12Ala G allele was significantly less frequent in PCOS versus control women (13,16). Additionally, some studies reported significant increases in insulin sensitivity (decreased HOMA-IR) and decreases in fasting insulin and glucose levels (8-10) and lower hirsutism score (9) in PCOS women with the Pro12Ala G allele; whereas others (7,11,14), including this study, reported no association with fasting glucose and insulin or changes in HOMA-IR in those with PCOS.…”
Section: Discussionmentioning
confidence: 64%
“…Distribution of PPARG Pro12Ala alleles and genotypes in PCOS patients and controls. the European population (25)(26)(27)(28)(29)(31)(32)(33)(34). To the best of our knowledge, the highest prevalence of the PPARG Pro12Ala polymorphism was reported in the Polish (23,15%) (37) and the Slovenian populations (27,5%) (38).…”
Section: Discussionmentioning
confidence: 99%
“…Although certain studies demonstrated a lower frequency of PPARG Pro12Ala polymorphism among PCOS patients (24)(25)(26), the majority of case-control studies (27)(28)(29)(30)(31)(32)(33)(34) reported no significant differences. However, the merged results of several case-control studies revealed that the carriers of the polymorphic Ala allele have a lower risk of developing PCOS (32, 35,36).…”
Section: Discussionmentioning
confidence: 99%